Protracted Security Threats at the Bangladesh- Myanmar Border: A Holistic Approach to Peace and Security - Trisha, Khurshida Khan (Academia Journal of Humanities & Social Sciences, 2026)
The Bangladesh-Myanmar border is one of the unstable regions in South Asia considering its complicated politics and security processes. This border is mixed with the multidimensional issues as well as political instability in Myanmar, including ineffective border controls, the Rohingya refugee crisis, and other unconventional security issues. This paper analyzes the security threats arising out of this porous border and possible solutions. This study has adopted a qualitative research methodology in which the literatures have been analyzed from the policy documents and respectable media sources. This assists in defining the major forces behind the border security and their effects on the national security of Bangladesh. The results indicate that the Rohingya crisis is now a constant menace that had boosted the illicit drug, arms, and human trafficking, and even a long term political instability in Myanmar and other cross-border crimes along the border. The border instability has also been augmented by the emergence of non-state actors like the Arakan Army in Myanmar's Rakhain State. This paper provides a holistic approach to the border management through the incorporation of proactive diplomacy, improved security coordination, and socio-economic development of border communities. This study is a contribution in the debate that still exists in regard to the border security and policy recommendation by emphasizing on the regional stability. Therefore, the paper aims to transform the Bangladesh-Myanmar border as a zone of instability to a zone of cooperation and stability.